1997
DOI: 10.1021/ic961128d
|View full text |Cite
|
Sign up to set email alerts
|

Labile Complexes of the [RuTp(pn)]+ (Tp = Tripyrazolylborate, pn = Ph2PCH2CH2NMe2) Fragment Including the Dinitrogen Ligand1

Abstract: The [TpRu(pn)](+) fragment (Tp = tripyrazolyl, pn = Ph(2)PCH(2)CH(2)NMe(2)), featuring a strong sigma acceptor and a weak pi donor, forms reversible complexes with a variety of sigma donor ligands L including N(2) which appears to be more strongly bonded than even CH(3)CN. X-ray crystal structures of the complexes with L = H(2)O, acetone, CO, N(2), and vinylidene are included (adding to that for L = CH(3)CN from former work), as well as a comparative MO study on the bonding nature of L. The sequence of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
14
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 48 publications
8
14
0
Order By: Relevance
“…In the IR spectrum the ν(C᎐ ᎐ O) band is observed at 1640 cm Ϫ1 , in line with other ruthenium dmf complexes. 5,12 This value is below that of free dmf observed at 1675 cm Ϫ1 , implying, as expected, that co-ordination decreases the C᎐ ᎐ O bond strength. The ν(B᎐H) vibration is found at 2480 cm Ϫ1 which is characteristic of HB(pz) 3 when terdentate N,NЈ,NЉ-bonded to a metal center.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…In the IR spectrum the ν(C᎐ ᎐ O) band is observed at 1640 cm Ϫ1 , in line with other ruthenium dmf complexes. 5,12 This value is below that of free dmf observed at 1675 cm Ϫ1 , implying, as expected, that co-ordination decreases the C᎐ ᎐ O bond strength. The ν(B᎐H) vibration is found at 2480 cm Ϫ1 which is characteristic of HB(pz) 3 when terdentate N,NЈ,NЉ-bonded to a metal center.…”
Section: Resultssupporting
confidence: 54%
“…C 32 H 31 BClN 6 O 2 PRu requires C, 54.14; H, 4.40; N, 11.84%). NMR (CDCl 3 , 20 ЊC): δ H 7.90 (d, 1 H, J = 2.0, borate), 7.71 (d, 1 H, J = 2.0, borate), 7.69 (d, 1 H, J = 2.4, borate), 7 H,Ph,borate),9 H,Ph),6.68 (d,1 H, J = 2.0, borate), 6.33 (d, 1 H, J = 2.0, borate), 6.19 (m, 1 H, borate), 5.93 (dd, 1 H, J = 2.0, 2.0, borate), 5.77 (dd, 1 H, J = 2.3, 2.3, borate), 4.70 (d, 1 H, 4 5 of Ph), 106.45 (d, 4 J CP = 2.5, borate), 106.35 (borate), 106.26 (d, 3…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar dinitrogen complexes with cyclopentadienyl (Cp) and hydrotris(pyrazolyl)borate (Tp) ligands have been reported earlier by Kirchner, Mereiter, Valerga, Puerta and Moro-oka. [21][22][23][24][25][26] In order to synthesize the dinitrogen complex 7 methodically, 6 was dissolved in THF under a dinitrogen atmosphere and stirred at room temperature. After a few minutes, a yellow solid started to precipitate from the initially red solution.…”
Section: Complexes With Bulky Co-ligandsmentioning
confidence: 99%
“…The inability to remove CH 3 CN thermally or to be displaced by terminal alkynes in these complexes is consistent with the stabilities of other ruthenium tris(pyrazolyl)borate acetonitrile complexes. For example, the stability of the complexes [(Tp)Ru(tmeda)L] ' (tmeda 0/Me 2 NCH 2 CH 2 NMe 2 ) was found to increase with L in the order L 0/THF B/CF 3 SO 3 B/acetone B/CH 3 CN :/DMF [73]. These workers also found that the CH 3 …”
Section: Discussionmentioning
confidence: 97%